Measurement of fusional vergence: protocol for a systematic review - Lança, Carla (2016)
Introduction - No validated protocol exists for the measurement of the prism fusion ranges. Many studies report on how fusional vergence ranges can be measured using different techniques (rotary prism, prism bar, loose prisms and synoptophore) and stimuli, leading to different ranges being reported in the literature. Repeatability of the different methods available and the equivalence between them it is also important. In addition, some studies available do not agree in what order fusional vergence should be measured to provide the essential information on which to base clinical judgements on compensation of deviations. When performing fusional vergence testing the most commonly accepted clinical technique is to first measure negative fusional vergence followed by a measurement of positive fusional vergence to avoid affecting the value of vergence recovery because of excessive stimulation of convergence. Von Noorden recommend using vertical fusion amplitudes in between horizontal amplitudes (base-out, base-up, base-in, and base down) to prevent vergence adaptation. Others place the base of the prism in the direction opposite to that used to measure the deviation to increase the vergence demand. Objectives - The purpose of this review is to assess and compare the accuracy of tests for measurement of fusional vergence. Secondary objectives are to investigate sources of heterogeneity of diagnostic accuracy including: age; variation in method of assessment; study design; study size; type of strabismus (convergent, divergent, vertical, cycle); severity of strabismus (constant/intermittent/latent).